L’élaboration des stratégies de travail nocturnes : le cas d’infirmières de nuit d’un service de pneumologie français - Cathy Toupin (Perspectives Interdisciplinaires sur le Travail et la Santé)
The objective of this study is to evaluate the development, by night shift nurses, of « work strategies » specific to this nycthemer, and to demonstrate the role of professional experience in this construction. This reflection is consistent with the extension of ergonomic research that linked « age and experience », « atypical schedules » and « work activity » poles. The research linking these poles in pairs is abundant, but attempts to articulate these three dimensions are rare to our knowledge and hardly indicate how professional experience promotes or not the implementation of regulation in the performance of the activity itself.The study - carried out in a pneumology department in a French hospital - shows that night shift nurses develop different « work strategies » by redefining their own objectives and priorities in the goals, considering the particular features of hospital life during this period (mainly the specific « condition » of patients during the night, and the « desert » environment of care services).Various components of occupational experience promote this development. Thus, experience (previous) with day nurse work, with the care unit’s work, and with night nurse work play a role in this reorganization by the night nurse of the activity’s goals and priorities in the nocturnal period.